2019
DOI: 10.1016/j.joep.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Identity changes and well-being gains of spending money on material and experiential consumer products

Abstract:  How a purchase is thought to transform one's sense of self by satisfying the different identity-related functions of distinctiveness, effectiveness, selfesteem, relatedness, and projected identity explains variance in expected and perceived well-being gains associated with consumer products above and beyond the material-experiential nature of a purchase.  The identity-related functions of effectiveness and self-esteem were consistently found to positively predict well-being, indicating that gaining a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“…After excluding 32 participants (13%) who failed the instructional manipulation check (e.g., “please click 3 for this question.”; He & Bond, 2015; Oppenheimer et al., 2009) or wrote wrong answers in the article summary or recall task, 214 participants (75.2% females, M age = 36.4) were included in the final analyses. This exclusion ratio is not higher than the exclusion ratios in previous studies on consumption and SWB (e.g., exclusion ratio in previous studies was 26.4% for Study 1 in Moldes et al., 2019; 25.8% for Study 2 in Guevarra & Howell, 2015; 33.7% for Study 3 in Guevarra & Howell, 2015; 17.7% for Study 2 in Caprariello & Reis, 2013). Ethnic distribution was as follows: 92.1% white, 3.7% mixed or multiple ethnic groups, 2.3% Asian or Asian British, and 1.9% Black, Black British, African, or Caribbean.…”
Section: Methodscontrasting
confidence: 53%
“…After excluding 32 participants (13%) who failed the instructional manipulation check (e.g., “please click 3 for this question.”; He & Bond, 2015; Oppenheimer et al., 2009) or wrote wrong answers in the article summary or recall task, 214 participants (75.2% females, M age = 36.4) were included in the final analyses. This exclusion ratio is not higher than the exclusion ratios in previous studies on consumption and SWB (e.g., exclusion ratio in previous studies was 26.4% for Study 1 in Moldes et al., 2019; 25.8% for Study 2 in Guevarra & Howell, 2015; 33.7% for Study 3 in Guevarra & Howell, 2015; 17.7% for Study 2 in Caprariello & Reis, 2013). Ethnic distribution was as follows: 92.1% white, 3.7% mixed or multiple ethnic groups, 2.3% Asian or Asian British, and 1.9% Black, Black British, African, or Caribbean.…”
Section: Methodscontrasting
confidence: 53%
“…Furthermore, even though lockdown restrictions and “stay‐at‐home” recommendations limited consumer spending choices and shifted habits towards material consumption, 4 we do not find a change in the preference for material spending over experiential consumption. In fact, it is possible that the increase in negative affect may partially be a consequence of frustrated experiential spending due to lockdown restrictions, given that experiential consumption has been found to bring more happiness (Van Boven & Gilovich, 2003 ) and to improve one's self‐esteem, sense of uniqueness, and relatedness (Moldes et al, 2019 ) than material purchases.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been found that priming money to low‐social‐class students can help to decrease materialistic desires (as shown in Li et al, 2018). We excluded all studies that asked participants to describe a material purchase (against participants describing an experiential one), because participants in both conditions were reminded about spending behaviors, and recent research has found that experiential consumer products fulfill conspicuous consumption desires as much as material ones (Moldes, Banerjee, Easterbrook, Harris, & Dittmar, 2019). We excluded manipulations that framed a specific task (such as recycling or exercise) by highlighting the intrinsic or self‐transcendent goals against extrinsic or self‐enhancement motives for performing the task (e.g., Evans et al, 2013; Vansteenkiste, Matos, Lens, & Soenens, 2007), as these manipulations might have changed the participants' orientations when carrying out the task (learning or exercise), but do not necessarily make salient a materialistic focus or consumer culture ideals.…”
Section: Methodsmentioning
confidence: 99%